Karakteristik Tanah Andisol Pasca Konversi Lahan Hutan Menjadi Semak - Anindita, Sastrika; Sandrawati, Apong; Arifin, Mahfud; Devnita, Rina (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
Land use conversion can affect characteristics of soil and also soil quality. The present study evaluate theimpact of land use conversion from pine forest to bush in tropical volcanic soils in Indonesia. We comparedtwo soil profiles from the same areas (uphill slope of Mt. Tangkuban Perahu) and analysed theirmorphological, physical, and chemical soil properties. Our study showed that there was a decrease in soilorganic carbon stock about 3.7% (382 ton C ha-1) after approximately 8-15 years of land conversion. Other physical and chemical soil properties, such as soil texture, bulk density, pH, exchangeable base and acidity,cation exchange capacity, and base saturation were relatively similar. This research provide insight intohow change in vegetation cover can affect carbon and nutrient dynamics as well as become a baseline tounderstand soil recovery potential if the land is restored to forest or bush in volcanic soils.